Single nucleotide polymorphism (SNP) rs3751143 in P2RX7 is associated with therapy failure in chronic Q fever while rs7125062 in MMP1 is associated with fewer complications. (May 2021) - Buijs, S.B.; Jansen, A.F.M.; Oosterheert, J.J.; Schoffelen, T.; Wever, P.C.; Hoepelman, A.I.M.; van de Vosse, E.; van Deuren, M.; Bleeker-Rovers, C.P.
Abstract: Objectives: Chronic Q fever is a persistent infection with the intracellular bacterium Coxiella burnetii. Development of chronic Q fever is associated with single nucleotide polymorphisms (SNPs) in genes encoding for pattern recognition receptors, for phagolysosomal pathway components and for matrix metalloproteinases (MMPs). We evaluated the association of SNPs in these innate-immunity and MMP genes with clinical outcomes. Methods: SNPs were selected from previous association studies and analysed in a cohort of patients with chronic Q fever. The primary outcome was all-cause mortality; secondary outcomes were therapy failure and chronic Q fever–related complications. Subdistribution hazard ratios (SHR) were calculated. Results: Nineteen SNPs were analysed in 134 patients with proven and 29 with probable chronic Q fever. In multivariable analysis, none of the selected SNPs was associated with all-cause mortality. However, SNP rs3751143 located in P2RX7 appeared to be associated with therapy failure (SHR 2.42; 95% confidence interval, 1.16–5.05; p 0.02), which is in line with other reports, showing that a loss of function of the P2X7 receptor leads to inefficient killing of intracellular organisms. In addition, SNP rs7125062 located in MMP1, involved in the cleavage of extracellular matrix, was associated with fewer chronic Q fever–related complications such as acute aneurysms (SHR 0.49; 95% confidence interval, 0.29–0.83; p 0.008). Conclusions: A polymorphism in P2RX7, known to lead to loss of function of the receptor and inefficient killing of intracellular organisms, and a polymorphism in MMP1 were respectively associated with more therapy failures and fewer complications such as acute aneurysms in patients with chronic Q fever.